Highly Sensitive Electrochemical Sensor Modified with Pt/Pd-MnO2/CNT Nanocomposite for the Determination of Glutamate - Math, Chim; Duenchay, Paweenar; Dungchai, Wijitar (Trends in Sciences, 2025)
A novel nanocomposite comprising platinum/palladium-decorated manganese dioxide on carbon nanotubes (Pt/Pd-MnO2/CNT) was successfully synthesized and immobilized onto a screen-printed carbon electrode (SPCE) for the electrochemical detection of glutamate. The electrocatalytic performance of the modified electrode was systematically evaluated using cyclic voltammetry (CV) and chronoamperometry (CA). Conventional glutamate biosensors that rely on the immobilization of glutamate oxidase often encounter several limitations, including high detection limits, electrode fouling, and poor operational stability, primarily due to enzyme leaching or denaturation. In contrast, the proposed sensor circumvents the need for enzyme immobilization on electrode by utilizing an electrocatalytic approach. This strategy maintains a high degree of analyte selectivity while significantly improving the sensor’s stability, reproducibility, and overall analytical performance. The resulting sensor exhibited high sensitivity, with a detection limit of 1.98 µM, surpassing previously reported values. It demonstrated a linear response in the range of 0.005 - 0.08 mM and showed excellent selectivity by minimizing interference from common electroactive species such as ascorbic acid (AA) and uric acid (UA), thanks to a reduction-based detection mechanism. The sensor also exhibited strong durability, retaining 96 % of its initial signal after 3 weeks of storage. Furthermore, it demonstrated excellent repeatability and reproducibility, as well as high resistance to common interferences. Validation studies conducted on spiked samples showed recovery rates between 99 and 105 %, confirming the method’s precision and accuracy. The practical application of the sensor was demonstrated through the quantification of glutamate in various instant noodle seasoning samples. The amounts of glutamate detected were 63.55 mg in Shrimp Tom Yum, 127.23 mg in Yentafo Tom Yum Mohfai, and 82.91 mg in Shrimp Creamy Tom Yum seasoning packets, respectively. In summary, the Pt/Pd-MnO2/CNT-modified electrode offers a reliable, sensitive, and selective platform for real-time electrochemical detection of glutamate in complex food matrices, highlighting its potential for application in food safety and quality control. HIGHLIGHTS A newly developed glutamate biosensor utilizing a Pt/Pd-MnO₂/CNT electrode enables efficient glutamate detection. The sensor demonstrates high selectivity, contributing to its cathodic current detection. The sensor exhibits high sensitivity, accuracy, and stability. The sensor was successfully applied to detect glutamate in food samples. GRAPHICAL ABSTRACT